Ultrasound and anatomical correlation of the radial nerve at the arcade of Frohse. Issue 6 (24th April 2015) - Meng, Stefan; Tinhofer, Ines; Weninger, Wolfgang J.; Grisold, Wolfgang
ABSTRACT Introduction In this anatomical study we evaluated the feasibility of ultrasound (US) guided perineural injection of the deep branch of the radial nerve (DBRN) at the arcade of Frohse as potential therapy for nerve entrapment at this site. Methods We examined 21 arms from 11 nonembalmed cadavers with US. Under US guidance, we injected ink into the DBRN perineural sheath beneath the arcade of Frohse. In subsequent anatomical dissection we evaluated the distribution of the ink. Results It was possible to apply ink at the DBRN in 95%. In 80% the ink remained within the supinator and did not reach the DBRN segment proximal to the arcade. Conclusions With US guidance, it is possible to apply injection fluid safely around the DBRN inside the supinator tunnel. Due to the limited extent of the fluid, a second injection proximal to the arcade should be considered in the clinical setting. Muscle Nerve51: 853–858, 2015